FROM POLICY TO PRACTICE: STRENGTHENING HEALTH SYSTEMS THROUGH EVIDENCE, EQUITY, AND INNOVATION - Haerawati Idris (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2026)
Health systems worldwide are confronting increasingly complex challenges driven by demographic and epidemiological shifts transitions, technological advance, emerging health threats. Achieving Universal Health Coverage (UHC) and the Sustainable Development Goals (SDGs) therefore requires health systems that are not only accessible but also resilient, evidence-informed, and people-centered. This editorial synthesizes the contributions of the studies published in this issue through four interconnected dimensions of health system strengthening: governance and policy, service delivery and quality, the health workforce, and equity and innovation. The articles demonstrate that effective governance depends on translating evidence into coherent policies and successful implementation across different levels of the health system. High-quality service delivery requires organizational readiness, patient-centered care, and continuous quality improvement, while a resilient health workforce relies on supportive leadership, workforce well-being, and enabling work environments. The studies further highlight the importance of addressing social and geographic inequities and ensuring that technological innovations are implemented equitably to improve health outcomes across diverse populations. Together, these contributions reinforce the need for integrated, multisectoral, and evidence-informed strategies that connect governance, service delivery, workforce development, and equitable innovation. Strengthening these interconnected components is essential for building resilient health systems capable of responding to current challenges. Keyword: health systems, Universal Health Coverage, health policy.